EDUCATIONAL COURSES IN HEALTH: ORGANIZATIONAL PRODUCTIVITY (Fiep Bulletin - online, 2011)
We aim at studying the importance of health in people's lives (employees) and companies (organizations), in broad terms, identifying the contribution that institutions can give to their Human Resources in order to improve the quality of life, through the promotion of training courses and training whose purpose is to make people more aware of their healthy living habits. Understanding the 'quality of life' and its reflection / influence on the employees' health was the analysis focus, aiming at recognizing myths and prejudice when it causes damage to the quality of life and its impacts on the Human Resources' health, where our goal was to detect the experiences of health educational courses sponsored by SRH and DSA from the Federal University of Paraiba – UFPB. We used, methodologically, two investigative tools: literature review and field research (applying mixed-questions questionnaires - questions to choose the right answer and to comment on a topic and direct observations form). The population of the research comprised 147 (one-hundred and forty-seven) employees (teachers and staff members) from the mentioned university, active participants - as students – of the courses, including a sample of 28 (twenty-eight) workers – 6 (six) physiotherapy teachers and 22 (twenty-two) staff members distributed into two promotional educational courses – Gerontology Education in Health and From Stress to Well-Being – offered at the time this work was done, originated from the Specialization in Hospital Administration and Health Services course, of the Administration Department, from the Center of Applied Social Sciences – CCSA, Campus I, in UFPB, which had the author of this article as one of its students, as well as researcher in all steps of this monographic work, what produced this essay (article – work – text).
Keywords: Education; Health; Production